Examining urban tourists’ attitudes: The case study of Belgrade (Serbia) - Podovac, Milena; Ivanović, Slobodan; Milojica, Vedran (Turyzm/Tourism, 2023)
Personal characteristics have an important role in shaping tourists’ attitudes. The purpose of this study is to examine tourists’ attitudes to elements of the tourist offer of the city of Belgrade, the main urban destination in the Republic of Serbia. The primary research aim is to examine the influence of these personal characteristics on such attitudes. A survey was conducted on a sample of 319 tourists, who visited the city. The collected data were processed in the statistical program SPSS25 while the formed hypotheses were tested using appropriate statistical tests. The research results indicated that tourists highly rated the diversity of the gastronomic offer and the quality of nightlife, while organized tours for visiting tourist attractions and the quality of traffic infrastructure were ranked as elements in which there are opportunities for improvement. Further, the research results showed that origin and education influenced differences in tourists’ attitudes. The theoretical and practical implications as well as research limitations are defined, and recommendations made for the future research based on the theoretical background and research results.